Industrial tailing premixed mortar and preparation method thereof

By preparing industrial waste slag into ultrafine ore powder and mixing evenly with ternary composite alkali stoking agent and admixture, a premixed mortar with low application cost, good use effect and environmental protection of solid waste utilization ultrafine ore powder is prepared, which solves the low utilization rate and environmental pollution of industrial waste slag, and achieves efficient utilization and environmental protection effects.

CN119638281APending Publication Date: 2025-03-18EDSONBURG NEW MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411716934.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-27
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

Due to the low utilization rate of industrial waste slag and environmental pollution problems, it is difficult to effectively utilize the existing technology and improve its environmental impact.

Method used

By preparing industrial waste slag into ultrafine ore powder and mixing it evenly with ternary composite alkali trigger and admixture, a premixed mortar of solid waste with low application cost, good use effect and environmentally friendly is prepared.

Benefits of technology

It realizes efficient utilization of industrial waste slag, reduces production costs, reduces environmental pollution, and the prepared premixed mortar has good mechanical properties and thermal insulation properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119638281A_ABST
    Figure CN119638281A_ABST
Patent Text Reader

Abstract

The invention discloses industrial tailing premixed mortar and a preparation method thereof, and relates to the technical field of building material preparation. The cementing material of the industrial tailing premixed mortar is prepared by preparing industrial waste slag raw materials into superfine mineral powder to replace part of cement, and uniformly stirring the superfine mineral powder with a ternary composite alkali activator and a series of additives. The premixed mortar comprises the following components: cement, industrial tailing ultrafine powder, an alkali activator, cellulose and a water reducing agent, the preparation method specifically comprises the following steps: activation of an industrial waste slag raw material, preparation of a ternary composite alkali activator solution, preparation of premixed mortar slurry, molding, maintenance, and optimization of a process for preparing the premixed mortar. The inorganic cementing material disclosed by the invention is green, energy-saving and environment-friendly, is beneficial to reduction of carbon emission, and has popularization value; the application of the material accords with the development trend of the current society, and the material has good economic benefits and social benefits.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of building material preparation, and in particular relates to an industrial tailings premixed mortar and a preparation method thereof. Background Art

[0002] In recent years, my country's premixed mortar industry has developed rapidly, with a growing variety of products and an increasingly wide range of applications. As a new type of building material, premixed mortar has been vigorously promoted by the country due to its diversity, excellent performance, environmental protection characteristics and the ability to improve the efficiency of mechanized construction. At present, my country is actively promoting the use of industrial waste to produce premixed mortar, which not only effectively reduces production costs and improves mortar performance, but also makes important contributions to promoting green development and improving environmental quality. As an important inorganic cementitious material, cement is widely used in construction, roads, water conservancy, national defense and other projects, making significant contributions to human development and progress. However, due to its high energy consumption and high emission characteristics, the large-scale use of cement will lead to excessive consumption of resources and energy, bring serious environmental pollution and carbon emission problems, and put tremendous pressure on the optimization of ecological environment quality and pollution reduction and carbon reduction.

[0003] Industrial waste slag is a waste produced in the process of pig iron production, and its main component is SiO 2 and Al 2 O 3 , which is suitable for use as a raw material for the preparation of ultrafine mineral powder cement. The use of industrial waste slag powder in the preparation of ultrafine mineral powder premixed mortar can not only save costs, but also turn waste into treasure. Industrial waste slag is mainly produced in the process of pig iron production. Under normal circumstances, about 300 kg of granulated blast furnace slag can be produced for every ton of pig iron produced. As a major steel producer in the world, my country's pig iron industry has gradually matured, and its output has shown a steady growth in recent years, reaching an annual emission of 250 million tons. Due to its large particle size and poor activity, the utilization rate of industrial slag is still relatively low. Large-scale emissions and accumulation not only occupy land resources, but also cause serious pollution to the natural environment. Whether from the perspective of ecological environment improvement or solid waste utilization, the use of appropriate methods to modify industrial slag is of great value in improving the utilization rate of industrial slag and protecting the environment. Summary of the invention

[0004] The present invention provides an industrial tailings premixed mortar and a preparation method thereof. The mortar uses ultrafine mineral powder of industrial waste slag as the main raw material, and provides a supporting preparation method. Through the action of a polybasic activator, a low-cost, good-effect, and environmentally friendly solid waste utilization ultrafine mineral powder premixed mortar can be prepared, thereby solving the problems in the background technology.

[0005] In order to solve the above technical problems, the present invention is achieved through the following technical solutions:

[0006] The industrial tailings premixed mortar of the present invention adopts ultrafine mineral powder prepared from industrial waste slag to replace a certain proportion of cement as a gelling material, and is mixed evenly with a ternary composite alkali activator and an admixture;

[0007] The mass ratio of the alkali activator to the gelling material is 12.4%;

[0008] The ternary composite alkali activator is prepared from analytically pure sodium hydroxide, liquid water glass and anhydrous calcium sulfate, with a modulus of 1.4; the analytically pure sodium hydroxide is a white crystalline solid with a purity of ≥98%; the liquid water glass is a white transparent liquid with a modulus of 3.29; wherein SiO 2 and Na 2 The mass fractions of O are 26% and 9.15% respectively, that is, the solid content is 34.15%; the anhydrous calcium sulfate is a white powdery solid with a purity of ≥98%;

[0009] The additives are water reducer, thickener and plasticizer powder; the water reducer is FK-A type water reducer, which is a cream-yellow powder, has a water reduction rate of 45% and an air content of 2.5%; the thickener is hydroxypropyl methylcellulose, i.e., HPMC thickener, which is a white powder, has a viscosity of 250,000 Pa·s, a fineness range of 80-100 mesh, and a pH value of the aqueous solution of 7;

[0010] The industrial waste slag is a highly active slag, the average particle size of which is less than 10.6 μm and the activity coefficient of the ultrafine mineral powder is 0.51;

[0011] The cement is P·O 42.5 grade cement, the average particle size of which is less than 20.4 μm and the activity coefficient is 0.19.

[0012] A method for preparing an industrial tailings premixed mortar is used to prepare the above industrial tailings premixed mortar, comprising the following steps:

[0013] Step a, activation of ultrafine powder of industrial waste slag: ball milling the dried industrial waste slag powder for 12 hours to obtain ultrafine powder of slag with high activity;

[0014] Step b, preparing an alkali activator solution: adding analytically pure sodium hydroxide to liquid water glass and mixing to prepare a binary composite alkali activator with a modulus of 1.4, then adding anhydrous calcium sulfate, and subjecting to ultrasonic and stirring treatment to obtain a uniformly dispersed ternary composite alkali activator solution; taking out the above-mentioned uniformly stirred alkali activator solution, sealing the cup mouth with a polyethylene film, and aging it for later use;

[0015] Step c, preparing hydroxypropyl methylcellulose bonding solution:

[0016] Process ①: Powdered hydroxypropyl methylcellulose without any pre-treatment

[0017] Process ②: Take some test water, dissolve hydroxypropyl methylcellulose in water and stir it thoroughly with an electric stirrer to make it viscous, then let it stand for later use

[0018] Step d, preparing cement slurry:

[0019] Process ①: Powdered hydroxypropyl methylcellulose is directly poured into a mixer as a dry material together with a gelling material, a ternary composite alkali activator solution, a water reducing agent and plasticizing powder to prepare cement paste.

[0020] Process ②: first weigh the prepared slag ultrafine powder, cement and water reducer and fully dry mix them, then pour the ternary composite alkali activator solution and hydroxypropyl methylcellulose bonding solution into the mixer, and fully stir them evenly under the fixed condition of a water-to-solid ratio of 0.4;

[0021] Step e, molding: injecting the cement slurry prepared in step d into a pre-customized plate molding mold, placing the mold on a vibration table for compaction, then flattening the mold surface and covering it with a polyethylene film;

[0022] Step f, curing: Place the sample in step e in a standard curing room for 24 hours and then remove the mold. Place the sample after demolding in a standard constant temperature and humidity curing box for further curing.

[0023] Furthermore, the aging time of the alkaline activator obtained in step b is not less than 12 hours.

[0024] Furthermore, the industrial waste slag powder is ball-milled using a planetary ball mill.

[0025] Compared with the prior art, the present invention has the following beneficial effects:

[0026] (1) The premixed mortar of this scheme uses ultra-fine powder of industrial waste slag as the main raw material, which reduces the impact of the accumulation of industrial waste slag on the environment and has positive social and environmental benefits; making full use of industrial waste slag not only realizes its high added value utilization, but also saves resources and effectively reduces the production cost of premixed mortar, which has obvious economic and social benefits;

[0027] (2) The industrial waste slag ultrafine mineral powder of this scheme has been activated and tested to have an activity coefficient of 0.51, which has a high reaction activity. Under the action of the ternary composite alkali activator, an inorganic gel phase is generated. The prepared ultrafine mineral powder premixed mortar has good mechanical properties and thermal insulation properties. The ultrafine mineral powder premixed mortar uses industrial solid waste - slag micropowder, which not only turns waste into treasure, but also alleviates the problem of environmental pollution, which is beneficial to environmental protection;

[0028] (3) This scheme uses ultrafine powdered industrial waste slag as the main raw material, and uses an alkali activator to activate the ultrafine powdered industrial waste slag to prepare ultrafine powder premixed mortar. Industrial waste slag is a solid waste produced after iron smelting combustion. It has low activity and large accumulation volume. The rational and effective use of industrial waste slag is not only beneficial to environmental protection, but also can enhance its economic value. The content of Si and Al elements in industrial waste slag is relatively high, and it can be used to prepare ultrafine powdered cement. Using ultrafine powdered industrial waste slag as the main raw material for preparing cement has the characteristics of no burning and no clinker. It is a green, energy-saving and environmentally friendly inorganic cementitious material, which is beneficial to reducing carbon emissions and has promotion value. The application of this material is in line with the current trend of social development and has good economic and social benefits.

[0029] (4) The plasticizing powder of the present invention can be added to cement mortar to reduce water bleeding rate, improve workability, and increase impermeability and mortar strength.

[0030] Of course, any product implementing the present invention does not necessarily need to achieve all of the advantages described above at the same time. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings required for describing the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without paying creative work.

[0032] Figure 1 The particle size distribution diagram of the ultrafine mineral powder of industrial waste slag selected for the present invention;

[0033] Figure 2 Particle size distribution diagram of the cement selected for the present invention. DETAILED DESCRIPTION

[0034] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0035] An industrial tailings premixed mortar adopts ultrafine mineral powder prepared from industrial waste slag to replace a certain proportion of cement as a cementitious material, and is mixed evenly with a ternary composite alkali activator and an admixture; the mass ratio of the alkali activator to the cementitious material is 12.4%; the ternary composite alkali activator is prepared from analytically pure sodium hydroxide, liquid water glass and anhydrous calcium sulfate, and the modulus is 1.4; the analytically pure sodium hydroxide is a white crystalline solid with a purity of ≥98%; the liquid water glass is a white transparent liquid with a modulus of 3.29; wherein SiO 2 and Na 2 The mass fractions of O are 26% and 9.15% respectively, that is, the solid content is 34.15%; anhydrous calcium sulfate is a white powdery solid with a purity of ≥98%;

[0036] The additives are water reducer, thickener and plasticizer powder; the water reducer is FK-A type water reducer, which is a cream-yellow powder, with a water reduction rate of 45% and an air content of 2.5%; the thickener is hydroxypropyl methylcellulose, i.e. HPMC thickener, which is a white powder, with a viscosity of 250000 Pa·s, a fineness range of 80-100 mesh, and a pH value of the aqueous solution of 7;

[0037] The plasticizing powder is composed of a filler and a surfactant, wherein the filler includes kaolin and / or slag, and the surfactant is sodium α-olefin sulfonate;

[0038] Industrial waste slag is a highly active slag with an average particle size of less than 10.6 μm and an ultrafine powder activity coefficient of 0.51. Figure 1 As shown; the cement used is P·O 42.5 grade cement, its average particle size is less than 20.4μm, and its particle size distribution is as follows Figure 2 As shown, the activity coefficient is 0.19.

[0039] A method for preparing an industrial tailings premixed mortar is used to prepare the above industrial tailings premixed mortar, comprising the following steps:

[0040] Step a, activation of ultrafine powder of industrial waste slag: ball milling the dried industrial waste slag powder for 12 hours to obtain ultrafine powder of slag with high activity; the industrial waste slag powder is ball milled in a planetary ball mill;

[0041] Step b, preparing an alkali activator solution: adding analytically pure sodium hydroxide to liquid water glass and mixing to prepare a binary composite alkali activator with a modulus of 1.4, then adding anhydrous calcium sulfate, and preparing a uniformly dispersed ternary composite alkali activator solution through ultrasonic and stirring treatment; taking out the above-mentioned uniformly stirred alkali activator solution, sealing the cup mouth with a polyethylene film, and aging it for use; the aging time of the obtained alkali activator is not less than 12 hours;

[0042] Step c, preparing hydroxypropyl methylcellulose bonding solution:

[0043] Process ①: Powdered hydroxypropyl methylcellulose without any pre-treatment

[0044] Process ②: Take some test water, dissolve hydroxypropyl methylcellulose in water and stir it thoroughly with an electric stirrer to make it viscous, then let it stand for later use

[0045] Step d, preparing cement slurry:

[0046] Process ①: Powdered hydroxypropyl methylcellulose is directly poured into a mixer as a dry material together with a gelling material, a ternary composite alkali activator solution, a water reducing agent and plasticizing powder to prepare cement paste.

[0047] Process ②: first weigh the prepared slag ultrafine powder, cement and water reducer and fully dry mix them, then pour the ternary composite alkali activator solution and hydroxypropyl methylcellulose bonding solution into the mixer, and fully stir them evenly under the fixed condition of a water-to-solid ratio of 0.4;

[0048] Step e, molding: injecting the cement slurry prepared in step d into a pre-customized plate molding mold, placing the mold on a vibration table for compaction, then flattening the mold surface and covering it with a polyethylene film;

[0049] Step f, curing: Place the sample in step e in a standard curing room for curing for 24 hours and then remove the mold. Place the demolded sample in a standard constant temperature and humidity curing box for further curing.

[0050] Embodiment 1:

[0051] (1) Weigh 524.1 g of ultrafine powder of industrial waste slag, 765.5 g of cement, and 6.4 g of water reducing agent, pour them into a mixer, dry mix them evenly and set aside; wherein.

[0052] (2) Weigh 99.5 g of water glass and 14.2 g of sodium hydroxide, stir them thoroughly, add 46.9 g of anhydrous calcium sulfate, and prepare a uniformly dispersed ternary composite alkali activator solution through ultrasonic and stirring treatment; take out the above-mentioned uniformly stirred alkali activator solution, seal the cup mouth with a polyethylene film, and age it for 12 hours before use.

[0053] (3) Weigh 2.6 g of HPMC thickener and 30 g of plasticizer powder; the filler is kaolin 25 and 5 g of sodium α-olefin sulfonate.

[0054] (4) Pour the ternary composite alkali activator solution, plasticizing powder and HPMC into a blender and mix them evenly to obtain a mixed slurry.

[0055] (5) The mixed slurry is injected into a customized plate forming mold, the mold is placed on a vibration table for compaction, and then the mold surface is scraped flat and covered with a polyethylene film to prevent water evaporation; the sample is placed in a standard constant temperature and pressure curing room for 24 hours and then removed from the mold. The obtained sample is then placed in a standard constant temperature and pressure curing box for further curing up to 28 days.

[0056] The fluidity of the solid waste ultrafine mineral powder premixed mortar obtained by this method is 161mm, the final setting time is 180min, and the density after curing is 1860kg / m 3 ; The 3d compressive strength value is 19.6MPa, and the 28d compressive strength value is 31.8MPa.

[0057] Embodiment 2:

[0058] (1) Weigh 524.1 g of ultrafine powder of industrial waste slag, 765.5 g of cement, and 10.3 g of water reducing agent, pour them into a mixer, dry mix them and set aside.

[0059] (2) Weigh 99.5 g of water glass and 14.2 g of sodium hydroxide, stir them thoroughly, add 46.9 g of anhydrous calcium sulfate, and prepare a uniformly dispersed ternary composite alkali activator solution through ultrasonic and stirring treatment; take out the above-mentioned uniformly stirred alkali activator solution, seal the cup mouth with a polyethylene film, and age it for 12 hours before use.

[0060] (3) Weigh 2.6 g of HPMC thickener and 30 g of plasticizer powder; the filler is kaolin 25 and 5 g of sodium α-olefin sulfonate.

[0061] (4) Pour the plasticized powder of the ternary composite alkali activator solution and HPMC into a blender and mix evenly to obtain a mixed slurry.

[0062] (5) The mixed slurry is injected into a customized plate forming mold, the mold is placed on a vibration table for compaction, and then the mold surface is scraped flat and covered with a polyethylene film to prevent water evaporation; the sample is placed in a standard constant temperature and pressure curing room for 24 hours and then removed from the mold. The obtained sample is then placed in a standard constant temperature and pressure curing box for further curing up to 28 days.

[0063] The fluidity of the solid waste ultrafine mineral powder premixed mortar obtained by this method is 166mm, the final setting time is 200min, and the density after curing is 1874kg / m 3 ; The 3d compressive strength value is 21.0MPa, and the 28d compressive strength value is 43.6MPa.

[0064] Embodiment 3:

[0065] (1) Weigh 524.1 g of ultrafine powder of industrial waste slag, 765.5 g of cement, and 12.9 g of water reducing agent, pour them into a mixer, dry mix them and set aside.

[0066] (2) Weigh 99.5 g of water glass and 14.2 g of sodium hydroxide, stir them thoroughly, add 46.9 g of anhydrous calcium sulfate, and prepare a uniformly dispersed ternary composite alkali activator solution through ultrasonic and stirring treatment; take out the above-mentioned uniformly stirred alkali activator solution, seal the cup mouth with a polyethylene film, and age it for 12 hours before use.

[0067] (3) Weigh 2.6 g of HPMC thickener and 30 g of plasticizer powder; the filler is kaolin 25 and 5 g of sodium α-olefin sulfonate.

[0068] (4) Pour the ternary composite alkali activator solution, plasticizing powder and HPMC into a blender and mix them evenly to obtain a mixed slurry.

[0069] (5) The mixed slurry is injected into a customized plate forming mold, the mold is placed on a vibration table for compaction, and then the mold surface is scraped flat and covered with a polyethylene film to prevent water evaporation; the sample is placed in a standard constant temperature and pressure curing room for 24 hours and then removed from the mold. The obtained sample is then placed in a standard constant temperature and pressure curing box for further curing up to 28 days.

[0070] The solid waste ultrafine mineral powder premixed mortar obtained by this method has a fluidity of 184 mm and a final setting time of 240 min; the density after curing is 1802 kg / m3; the 3d compressive strength value is 17.6 MPa, and the 28d compressive strength value is 36.4 MPa.

[0071] Embodiment 4:

[0072] (1) Weigh 524.1 g of ultrafine powder of industrial waste slag, 765.5 g of cement, and 6.4 g of water reducing agent, pour them into a mixer, dry mix them and set aside.

[0073] (2) Weigh 99.5 g of water glass and 14.2 g of sodium hydroxide, stir them thoroughly, add 46.9 g of anhydrous calcium sulfate, and prepare a uniformly dispersed ternary composite alkali activator solution through ultrasonic and stirring treatment; take out the above-mentioned uniformly stirred alkali activator solution, seal the cup mouth with a polyethylene film, and age it for 12 hours before use.

[0074] (3) Weigh 2.6 g of HPMC thickener and 30 g of plasticizer powder; the filler is kaolin 25 and 5 g of sodium α-olefin sulfonate.

[0075] (4) Pour the ternary composite alkali activator solution, plasticizing powder and HPMC into a blender and mix them evenly to obtain a mixed slurry.

[0076] (5) The mixed slurry is injected into a customized plate forming mold, the mold is placed on a vibration table for compaction, and then the mold surface is scraped flat and covered with a polyethylene film to prevent water evaporation; the sample is placed in a standard constant temperature and pressure curing room for 24 hours and then removed from the mold. The obtained sample is then placed in a standard constant temperature and pressure curing box for further curing up to 28 days.

[0077] The fluidity of the solid waste ultrafine mineral powder premixed mortar obtained by this method is 149mm, the final setting time is 360min, the density after curing is 1789kg / m3, the 3d compressive strength value is 17.2MPa, and the 28d compressive strength value is 28.8MPa.

[0078] Embodiment 5:

[0079] (1) Weigh 524.1 g of ultrafine powder of industrial waste slag, 765.5 g of cement, and 10.3 g of water reducing agent, pour them into a mixer, dry mix them and set aside.

[0080] (2) Weigh 99.5 g of water glass and 14.2 g of sodium hydroxide, stir them thoroughly, add 46.9 g of anhydrous calcium sulfate, and prepare a uniformly dispersed ternary composite alkali activator solution through ultrasonic and stirring treatment; take out the above-mentioned uniformly stirred alkali activator solution, seal the cup mouth with a polyethylene film, and age it for 12 hours before use.

[0081] (3) Weigh 2.6 g of HPMC thickener and 30 g of plasticizer powder; the filler is kaolin 25 and 5 g of sodium α-olefin sulfonate.

[0082] (4) Pour the ternary composite alkali activator solution, plasticizing powder and HPMC into a blender and mix them evenly to obtain a mixed slurry.

[0083] (5) The mixed slurry is injected into a customized plate forming mold, the mold is placed on a vibration table for compaction, and then the mold surface is scraped flat and covered with a polyethylene film to prevent water evaporation; the sample is placed in a standard constant temperature and pressure curing room for 24 hours and then removed from the mold. The obtained sample is then placed in a standard constant temperature and pressure curing box for further curing up to 28 days.

[0084] The solid waste ultrafine mineral powder premixed mortar obtained by this method has a fluidity of 155mm and a final setting time of>1440min; the density after curing is 1765kg / m3; the 3d compressive strength value is 12.8MPa, and the 28d compressive strength value is 34.0MPa.

[0085] Embodiment 6:

[0086] (1) Weigh 524.1 g of ultrafine powder of industrial waste slag, 765.5 g of cement, and 10.3 g of water reducing agent, pour them into a mixer, dry mix them and set aside.

[0087] (2) Weigh 99.5 g of water glass and 14.2 g of sodium hydroxide, stir them thoroughly, add 46.9 g of anhydrous calcium sulfate, and prepare a uniformly dispersed ternary composite alkali activator solution through ultrasonic and stirring treatment; take out the above-mentioned uniformly stirred alkali activator solution, seal the cup mouth with a polyethylene film, and age it for 12 hours before use.

[0088] (3) Weigh 2.6 g of HPMC thickener, 30 g of plasticizer powder, 25 g of kaolin filler, and 5 g of sodium α-olefin sulfonate, pour into 559 g of water, stir thoroughly with an electric stirrer to make it viscous, and then let it stand for use.

[0089] (4) Pour the ternary composite alkali activator solution, plasticizing powder and HPMC binder solution into a blender and stir evenly to obtain a mixed slurry.

[0090] (5) The mixed slurry is injected into a customized plate forming mold, the mold is placed on a vibration table for compaction, and then the mold surface is scraped flat and covered with a polyethylene film to prevent water evaporation; the sample is placed in a standard constant temperature and pressure curing room for 24 hours and then removed from the mold. The obtained sample is then placed in a standard constant temperature and pressure curing box for further curing up to 28 days.

[0091] The solid waste ultrafine mineral powder premixed mortar obtained by this method has a fluidity of 160 mm and a final setting time of 170 min; the density after curing is 1878 kg / m3; the 3d compressive strength value is 22.4 MPa, and the 28d compressive strength value is 45.8 MPa.

[0092] Mix ratio design table of industrial tailings premixed mortar

[0093]

[0094]

[0095] By activating industrial waste slag and preparing industrial tailings premixed mortar with good working performance and excellent mechanical properties after the ternary composite alkali activator, not only a large amount of industrial waste slag can be disposed, but also the land resources occupied by solid waste storage can be reduced; the plasticizing powder of the present invention can be added to cement mortar to reduce water bleeding rate, improve workability, increase impermeability and mortar strength, and effectively solve the environmental problems caused by industrial waste.

[0096] Other unexplained parts of the present invention are the same as those of the prior art.

[0097] The preferred embodiments of the present invention disclosed above are only used to help illustrate the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to the specific implementation methods described. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.

Claims

1. An industrial tailings premix mortar, characterized in that: Ultrafine mineral powder made from industrial waste slag is used to replace a certain proportion of cement as a cementitious material, and is mixed evenly with a ternary composite alkali activator and an admixture; The mass ratio of the alkali activator to the gelling material is 12.4%; The ternary composite alkali activator is prepared from analytically pure sodium hydroxide, liquid water glass and anhydrous calcium sulfate, and the modulus is 1.4; The additives are water reducing agent, thickener and plasticizing powder; The industrial waste slag is a highly active slag, the average particle size of which is less than 10.6 μm and the activity coefficient of the ultrafine mineral powder is 0.51; The cement is P·O 42.5 grade cement, the average particle size of which is less than 20.4 μm and the activity coefficient is 0.

19.

2. The industrial tailings premix mortar according to claim 1, characterized in that: The water reducing agent is FK-A type water reducing agent, which is in the form of milky yellow powder, has a water reduction rate of 45% and an air content of 2.5%.

3. The industrial tailings premix mortar according to claim 1, characterized in that: The thickener is hydroxypropyl methylcellulose, which is in the form of white powder, has a viscosity of 250,000 Pa·s, a fineness range of 80-100 mesh, and a pH value of 7 in aqueous solution.

4. The industrial tailings premix mortar according to claim 1, characterized in that: The plasticizing powder is composed of fillers and surfactants. The fillers include kaolin and / or slag, and the surfactant is sodium α-olefin sulfonate.

5. The industrial tailings premix mortar according to claim 1, characterized in that: The sodium hydroxide is analytically pure and is a white crystalline solid with a purity of ≥98%.

6. The industrial tailings premix mortar according to claim 1, characterized in that: The liquid water glass is a white transparent liquid with a modulus of 3.29; wherein the mass fractions of SiO2 and Na2O are 26% and 9.15% respectively, that is, the solid content is 34.15%.

7. The industrial tailings premix mortar according to claim 1, characterized in that: The anhydrous calcium sulfate is a white powdery solid with a purity of ≥98%.

8. A method for preparing an industrial tailings premixed mortar, used for preparing an industrial tailings premixed mortar as claimed in claims 1-7, characterized in that: The steps include: Step a, activation of ultrafine powder of industrial waste slag: ball milling the dried industrial waste slag powder for 12 hours to obtain ultrafine powder of slag with high activity; Step b, preparing an alkali activator solution: adding analytically pure sodium hydroxide to liquid water glass and mixing to prepare a binary composite alkali activator with a modulus of 1.4, then adding anhydrous calcium sulfate, and subjecting to ultrasonic and stirring treatment to obtain a uniformly dispersed ternary composite alkali activator solution; taking out the above-mentioned uniformly stirred alkali activator solution, sealing the cup mouth with a polyethylene film, and aging it for later use; Step c, preparing hydroxypropyl methylcellulose bonding solution: Process ①: Powdered hydroxypropyl methylcellulose without any pre-treatment Process ②: Take some test water, dissolve hydroxypropyl methylcellulose in water and stir it thoroughly with an electric stirrer to make it viscous, then let it stand for later use Step d, preparing cement slurry: Process ①: Powdered hydroxypropyl methylcellulose is directly poured into a mixer as a dry material together with a gelling material, a ternary composite alkali activator solution, a water reducing agent and plasticizing powder to prepare cement paste. Process ②: first weigh the prepared slag ultrafine powder, cement and water reducer and fully dry mix them, then pour the ternary composite alkali activator solution and hydroxypropyl methylcellulose bonding solution into the mixer, and fully stir them evenly under the fixed condition of a water-to-solid ratio of 0.4; Step e, molding: injecting the cement slurry prepared in step d into a pre-customized plate molding mold, placing the mold on a vibration table for compaction, then flattening the mold surface and covering it with a polyethylene film; Step f, curing: Place the sample in step e in a standard curing room for curing for 24 hours and then remove the mold. Place the demolded sample in a standard constant temperature and humidity curing box for further curing.

9. The method for preparing an industrial tailings premixed mortar according to claim 7, characterized in that: The aging time of the alkaline activator obtained in step b is not less than 12 hours.

10. The method for preparing an industrial tailings premixed mortar according to claim 7, characterized in that: The industrial waste slag powder is ball-milled by a planetary ball mill.